Targeting the initiation and termination codons of SARS-CoV-2 spike protein as possible therapy against COVID-19: the role of novel harpagide 5-O-β-D-glucopyranoside from Clerodendrum volubile P Beauv. (Labiatae). Issue 6 (13th April 2022) - Erukainure, Ochuko L.; Atolani, Olubunmi; Muhammad, Aliyu; Katsayal, Sanusi B.; Ebhuoma, Osadolor O.; Ibeji, Collins U.; Mesaik, M. Ahmed
Abstract: The global spread of the coronavirus infections disease − 2019 (COVID-19) and the search for new drugs from natural products particularly from plants are receiving much attention recently. In this study, the therapeutic potential of a new iridoid glycoside isolated from the leaves of Clerodendrum volubile against COVID-19 was investigated. Harpagide 5-O-β-D-glucopyranoside (HG) was isolated, characterised and investigated for its druglikeness, optimized geometry, and pharmacokinetics properties. Its immunomodulatory was determined by chemiluminescence assay using polymorphonuclear neutrophils (PMNs) in addition to T-cell proliferation assay. In silico analysis was used in determining its molecular interaction with severe acute respiratory syndrome coronavirus-2 (SARS-COV-2). HG displayed potent druglikeness properties, with no inhibitory effect on cytochrome P450 (1A2, 2C19, 2C9, 2D6 and 3A4) and a predicted LD50 of 2000 mg/kg. Its 1 H-NMR chemical shifts showed a little deviation of 0.01 and 0.11 ppm for H-4 and H-9, respectively. HG significantly suppressed oxidative bursts in PMNs, while concomitantly inhibiting T-cell proliferation. It also displayed a very strong binding affinity with the translation initiation and termination sequence sites of spike (S) protein mRNA of SARS-COV-2, its gene product, and host ACE2 receptor. These results suggest the immunomodulatory properties and anti-SARS-COV-2 potentials of HG which can be explored in the treatment and management of COVID-19. Communicated by Ramaswamy H. Sarma